General principals of emergency poisoning treatment in the general practice office – challanges and obstacles - Lazarevic, Marija ž (General Practice, 2024)
Introduction. Timely recognition of acute or chronic poisoning, as well as the pharmacodynamic mechanisms and pathophysiology of poisoning, is of the utmost importance in the general practice office. Objective. We aimed to find out the rate of awareness and education of primary healthcare physicians on necessary measures in the case of poisoning treatment. Method. Physicans working in general practice in the Republic of Serbia were sent an electronic questionnaire ’’Urgent poisoning treatment in the general practice office’’. The questionnaire had 13 questions referring to the physician’s practical experience. Results. The rise of medication, product, and biological substance poisoning rate was registered at the primary healthcare level in the last five years and it went from 0,14 to 0,21. Poisoning with non-medical substances is on the steep decline, from 0,30 to 0,19 per 1000 inhabitants. We followed the experience of general physicians (GPs) from outpatient clinics, concerning the cases of acute and chronic poisoning, by examining the questionnaire which showed 71,43% of GPs met with this condition. Physicans were more likely to be met with accidental poisoning (41,07%), while (21,43%) were met with multiple intentional poisonings. A larger percentage of these cases (44,65%) were treated on-site. About the existence of the National Poisoning Control Center knew 53,57% of physicans and 58,93% were familiar with detoxication measures. Additional expertise in the area of poisoning is necessary in the opinion of 75% of physicians. Discussion. Poison intake, in different ways, into a body, may cause a patient’s death if not recognized on time, at the initial encounter in the general physician’s office. Conclusion. Awareness and education of the GPs in the outpatient clinics, as well as, readiness to learn additional skills proved to be an important factor in taking care of poisoned patients who call on their GPs first. Continuous education is a necessary measure for the improvement of healthcare quality in the treatment of acute and chronic poisoning.